Effects of ethanol on the properties of platelets and endothelial cells in model experiments - Stach-Jablonski, Ksenija; Kälsch, Anna-Isabelle; Weiß, Christel; Elmas, Elif; Borggrefe, Martin; Kälsch, Thorsten (World journal of cardiology, 2012)
Aim: To investigate effects of ethanol on activity markers of atherosclerosis in an in vitro endothelial cell model. Methods: After 24 h incubation with ethanol (0.0095%), human umbilical vein endothelial cells were stimulated for 1 h with lipopolysaccharide, and were then incubated in direct contact with activated platelets. Following this incubation, the expression of CD40L and CD62P on platelets, and the expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), urokinase plasminogen activator receptor (uPAR), and membrane-type 1 matrix metalloproteinase (MT1-MMP) on endothelial cells were measured by flow cytometry. Results: The increased expression of VCAM-1 and uPAR on endothelial cells by proinflammatory stimulation with activated platelets was significantly reduced through pre-incubation with ethanol (P < 0.05). Furthermore, platelets in direct contact with ethanol and with endothelial cells pre-incubated in ethanol showed a significant reduction in their CD40L expression (P < 0.05). Ethanol had no significant effect on ICAM-1 and MT1-MMP expression on endothelial cells. Conclusion: Ethanol directly attenuates platelet activation and has significant endothelial cell-mediated effects on selected markers of atherosclerosis in vitro. These findings underline possible protective effects of ethanol on atherosclerosis.